2000
DOI: 10.1177/0265407500173007
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sex Friends Who were Once Romantic Partners: Are they Platonic Friends Now?

Abstract: Relatively little is known about the relationships between exromantic partners. For example, is it possible for them to have a platonic friendship? The present study addresses this question by surveying both males and females who report having a cross-sex friend who was once a romantic partner and a cross-sex friend with whom there was never any romantic involvement. Both types of friendship are compared using rules of friendship, costs and benefits of friendship, romantic desires, and overall quality of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
43
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 21 publications
1
43
0
1
Order By: Relevance
“…More importantly perhaps, there appears to be greater acceptance now that former lovers or partners may sustain a friendship after their sexual involvement ends. Again, this is by no means a dominant pattern, but in some cases, people are able to modify the basis of a once romantic or sexual relationship, in some cases including their marriage, so that positive emotional and social involvement continues to characterize the tie (Budgeon, 2006; Fischer, De Graaf, & Kalmijn, 2005; Foley & Fraser, 1998; Schneider & Kenny, 2000). In this, heterosexual relationships are beginning to mirror gay male and lesbian partnerships in their postpartnership sustainability.…”
Section: Flexibility and Personal Relationshipsmentioning
confidence: 99%
“…More importantly perhaps, there appears to be greater acceptance now that former lovers or partners may sustain a friendship after their sexual involvement ends. Again, this is by no means a dominant pattern, but in some cases, people are able to modify the basis of a once romantic or sexual relationship, in some cases including their marriage, so that positive emotional and social involvement continues to characterize the tie (Budgeon, 2006; Fischer, De Graaf, & Kalmijn, 2005; Foley & Fraser, 1998; Schneider & Kenny, 2000). In this, heterosexual relationships are beginning to mirror gay male and lesbian partnerships in their postpartnership sustainability.…”
Section: Flexibility and Personal Relationshipsmentioning
confidence: 99%
“…However, Ahrons and Wallisch found that 40% of exspouses still desired interaction with their former spouse, even if no children were involved, and many reported that their former spouse was still their friend. Extending this research, social scientists have begun to examine relationships between former premarital dating partners (e.g., Lannutti & Cameron, 1999;Schneider & Kenny, 2000).…”
mentioning
confidence: 99%
“…VN dan AL memiliki pondasi yang kuat untuk menjalin persahabatan karena keduanya telah bersahabat cukup lama dan sudah mengenal satu sama lain dengan baik. Hubungan pertemanan memiliki potensi untuk terbentuk ketika laki-laki yang memiliki keinginan untuk mengakhiri hubungan romantis tersebut (Schneider & Kenny, 2000 (Schneider & Kenny, 2000). Indvidu yang menginginkan hubungan romantis akan melakukan kontak secara rutin, melakukan aktifitas bersama, dan sedikit atau tidak membicarakan hubungan romantis lainnya dibandingkan dengan individu yang ingin hubungannya tetap platonik (Guerrero & Chavez, 2005).…”
unclassified